KEANEKARAGAMAN JENIS ANGGREK ALAM DI DESA LEMBANTONGOA KECAMATAN PALOLO KABUPATEN SIGI - Zulkaidhah, Zulkaidhah; Mallombasang, Sri Ningsih; Ferdiansah, Ferdiansah (ForestSains, 2018)
As the largest island in Wallacea, Sulawesi is rich in biodiversity, of which most of flora and fauna are endemic. One of them is orchids. This study aims to investigate the species diversity, namely the number of the species and abundance of each species, as well as the species evenness of natural orchids in forest areas in Lembantongoa Village, Sigi district. This study was conducted for three months: February – April 2017. It was designed as an exploratory research with purposive sampling and systematic sampling as methods of sampling. The species diversity and species evenness of natural orchids were analyzed using species diversity index (H') and species evenness index (E). The findings of this study show that there are currently 15 genera and 30 species living naturally in the forest of Lembantongoa village, in which 25 species are epiphytic while 5 species are terrestrial. The diversity index is categorized as moderate, the species evenness index is relatively high and the species are evenly dispersed.